Generating symmetry-protected long-range entanglement - Shovan Dutta; Stefan Kuhr; Nigel R. Cooper (Physical Review Research, 2024)
Entanglement between spatially distant qubits is perhaps the most counterintuitive and vital resource for distributed quantum computing. However, despite a few special cases, there is no known general procedure to maximally entangle two distant parts of an interacting many-body system. Here we present a symmetry-based approach, whereby one applies several timed pulses to drive a system to a particular symmetry sector with maximal bipartite long-range entanglement. As a concrete example, we demonstrate how a simple sequence of on-site pulses on a qubit array can efficiently produce multiple stable nonlocal Bell pairs, realizable in present-day atomic and photonic experimental platforms. More generally, our approach paves a route for exotic state preparation by harnessing symmetry. For instance, we show how it allows the creation of long-sought-after superconducting η pairs in a repulsive Hubbard model.